2013
DOI: 10.1016/j.jns.2013.07.1805
|View full text |Cite
|
Sign up to set email alerts
|

Does pramipexole treatment improve headache in patients with concomitant migraine and restless legs syndrome?

Abstract: Background: Recent studies have suggested a strong link between migraines and restless legs syndrome (RLS). It is possible that these disorders share a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Dopamine antagonists relieve premonitory symptoms of migraine [30], whereas dopamine agonists are markedly effective in ameliorating RLS symptoms [18]. In contrast, our preliminary study showed that dopamine agonists may improve migraine headaches and RLS symptoms in patients with migraine with comorbid RLS [16]. Migraine headaches worsen with movement during attacks, whereas RLS symptoms improve with movement.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Dopamine antagonists relieve premonitory symptoms of migraine [30], whereas dopamine agonists are markedly effective in ameliorating RLS symptoms [18]. In contrast, our preliminary study showed that dopamine agonists may improve migraine headaches and RLS symptoms in patients with migraine with comorbid RLS [16]. Migraine headaches worsen with movement during attacks, whereas RLS symptoms improve with movement.…”
Section: Discussionmentioning
confidence: 79%
“…A significant association between RLS and migraine has been replicated in multiple case‐controlled and population‐based studies , and migraine is now considered to be a significant comorbid condition of RLS . Cross‐sectional studies have shown an increased prevalence of RLS in patients with migraine and relationships between RLS and headache‐related disabilities and sleep disturbances . However, there has been no prospective study evaluating the impact of RLS on clinical factors in patients with migraine and the clinical implications of comorbid RLS for patients with migraine have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed the effect of anti-RLS therapy on alterations in comorbid migraine. In a small (n = 10) study of patients with concomitant migraine and RLS, dopaminergic treatment with immediate-release pramipexole improved both RLS symptoms in all patients and headache frequency and severity in half over a period of 5 months [40]. Headache relief was also reported in another case study (n = 40) in one-third of migraineurs when treating RLS, most often when using dopamine-3 receptor agonists such as gabapentin or pregabalin [14].…”
Section: Discussionmentioning
confidence: 86%
“…Some migraine sufferers are hypersensitive to dopamine agonists, at risk for some symptoms such as yawning, nausea, drowsiness, mood changes, and food cravings [57]. Still, a recent paper reported treatment of ten RLS/WED plus migraine patients with pramipexole with 50 % improvement of migraine and 80 % of improvement in morning headache [59]. These data have to be weighted considering the distress caused by the symptoms of the sleep disorder in migraine versus direct harm of its use in migraine.…”
Section: Rls/wed and Migrainementioning
confidence: 99%